Energy management for Madhya Pradesh, India - Koh, Chien Shen. (2013)
The ever growing demand for energy is a serious concern in our present generation due to the increased amount of carbon emissions. It is important that we start to tap into the resources of renewable energy to prevent extensive damage to our planet as well as the depletion of natural resources. In this report, we focus on one of the emerging economies, India, and integrating renewable energy sources into the pre-existing grid through the usage of smart grids.